Changes in cetacean presence, relative abundance and distribution over 20 years along a trans‐regional fixed line transect in the Central Tyrrhenian Sea. (16th October 2012) - Arcangeli, Antonella; Marini, Luca; Crosti, Roberto
Abstract From 1989 to 1992, systematic cetacean surveys were carried out twice weekly along a trans‐regional fixed transect in the Central Tyrrhenian Sea, utilising passenger ferries as research platforms. Using the same protocol and supervised by the same investigators, the research restarted in 2007, providing the opportunity to compare consistent data over a long 20‐year period. The monitored transect (Civitavecchia‐Golfo Aranci) runs along a strategic area just outside the southeastern border of the Pelagos Sanctuary. Over the last two decades, an increasing trend of temperature and salinity, in the deep and intermediate layers, has been documented in the region, as well as general changes over the Mediterranean basin. These changes, together with the increasing impact of some pressures (e.g. maritime traffic) may have led to changes in oceanographic and anthropogenic features and, subsequently, in cetacean presence and distribution. The research aimed to verify whether any changes occurred in the pattern of cetacean occurrence over the 20‐year period along the representative transect in the Central Tyrrhenian Sea. Data from 90 summer weekly runs undertaken in the 1990s were compared with data obtained from 95 runs undertaken in the 2000s. Each ferry run was considered an independent statistical unit: the encounter rate (ER = number of sightings per hour spent on effort) was calculated to compare relative abundance between periods, years and months. Spatial analysis was performed on geographical data using Kernel analysis to map the distribution of sightings. Logistic regression (GLM) was performed to compare habitat preference. Total encounter rate in the 1990s (ER = 0.59 ± CI 0.08) was significantly lower (P < 0.01) compared with the 2000s (ER = 0.94 ± CI 0.15). The same seven out of eight species known for their regular presence in the Mediterranean Sea were sighted in both the investigated periods. The most common species were striped dolphin (Stenella coeruleoalba), fin whale (Balaenoptera physalus) and common bottlenose dolphin (Tursiops truncatus). Neither the pilot whale nor any other rare or occasional species were sighted during the 6 years of the study. Despite the time span, no dramatic changes were observed for any species, bar fin whale, in terms of distribution, relative abundance, group size or habitat preference. Sightings of fin whale have surprisingly increased (+300%, P< 0.001), and their spatial and temporal distribution and habitat preference showed a radical difference between the two periods. The 2000s surveys confirmed the existence of high density areas of cetaceans, especially of fin whale, and the consequent necessity of specific legislative acts for cetacean conservation.